Semantic Roles of Iḍāfah in Surah Az-Zumar 1-20 and Their Interpretive Implications - Farrada'biya Farrada'biya; Hunaidah Hunaidah; Agung Pranoto Kadiatmaja (STIKes Ibnu Sina Ajibarang, 2026)
This study aims to explore the semantic roles of iḍāfah constructions in the first 20 verses of Surah Az-Zumar and their theological implications based on the perspective of Tafsir As-Sa’di. The central problem addressed is the tendency of Quranic linguistic analysis to focus heavily on grammatical formalities (i’rāb), thereby neglecting its functional-semantic dimensions. This structural-formal reductionism risks obscuring the depth of the Quran's transcendental message, particularly in constructing the concept of monotheism (Tawhid). Employing a descriptive-analytical method within a qualitative library research framework, this study examines iḍāfah lingual units by synergizing Ibn ‘Aqil’s classical syntactic theory with functional semantics. Data were purposively collected using the note-taking technique, then textually analyzed and verified through literature data triangulation to ensure objectivity and interpretive accuracy. The results reveal 15 iḍāfah fragments, which are predominantly categorized as iḍāfah ma’nawiyyah, while iḍāfah lafẓiyyah is found in only one fragment. The findings identify several semantic roles grouped into three major thematic clusters: 1) Origin/Source roles that consolidate the authority of revelation, 2) Ownership and Relational/Honorific roles that define the proximity of the God-servant relationship, and 3) Agency and Legal Decree roles that establish human moral responsibility. The study concludes that the iḍāfah structure in the Quran is not merely a technical element but a theological instrument that transforms lexical meanings into profound and systematic concepts of monotheism.